Three dimensional digital reconstructions in the case study of 19th century house (Research Announcements "Heritage BG", 2025)
In this paper I present part of the cultural heritage in the archive 'Architecture' at the Institute of Art studies through the opportunities provided by the software technologies for three-dimensional digital architectural reconstructions. According to criteria I established, I developed a collection of ten architecturally recorded in the 1950s old buildings from the 19th century. I start the three-dimensional reconstructions with a house in the town of Nessebar, situated on the Black Sea coast. The research focus is to discover not only the technical and mathematical parameters of this building, but also philosophical and poetic aspects in the architecture. In some essential points of my analysis, I refer to the thesis of the American architect and researcher Peter Eisenman: firstly to his definition for a canonical building and secondly to his methodology of repetition in the close reading of architecture.The thesis I defend through the reconstruction is that this house is an office building made of wood and stone. Like Eisenman's methodology, I disassemble the original composition of the project into a series of components for rethinking. I look at the elements independently: yard, stairs, cavity, walls, chimney, windows. I find in the house the contrasting ideas of slowness and of acceleration. References:Agacinski 2006: Agacinski, Sylviane. Philosophies et politiques des l’ architecture. SofiaVazov 1964: Vazov, Ivan. Pod igoto. t. 3. Sachinenia. Sofia.Allen 2008: Allen, Stan. Eisenman’s canon. A counter-memory of the modern. In: Ten Canonical Buildings: 1950-2000. New-York, 9-12.Butcher 2020: Butcher, Matthew. Architectures of Slowness: Actioning Historical Loops and Repetitions. In: Expanding Field of Architectural Discourse and Practice, eds. Matthew Butcher, Megan O’Shea. London, 160-191.Eisenman 2008: Eisenman, Peter. Ten Canonical Buildings: 1950-2000. New York.Eisenman 2006: Eisenman, Peter. The Formal Basis of Modern Architecture. Zürich.Vitale 2016: Vitale, Valeria. Transparent, Multivocal, Crossdisciplinary: the Use of Linked Open Data and a Community – Developed RDF Ontology to Document and Enrich 3D Visualization for Cultural Heritage. In: Digital Classics Outside the Echo-chamber. Teaching, Knowledge Exchange and Public Engagement, eds. Gabriel Bodard, Matteo Romanello, London, 147-168.
Keywords: 3D; three-dimensional graphics; three-dimensional visualization; architecture